Problematika Pernikahan Dini yang Marak Terjadi di Indonesia Menurut Pandangan Hukum Perdata - Azizah, Nur (Indra Institute Research & Publication, 2024)
Indonesia is ranked 8th in the world and 2nd in ASEAN in the most cases of early marriage. This research uses the literature study method in which the main problems are (1) what is meant by early marriage, (2) the view of civil law on early marriages that occur in Indonesia, (3) the factors that cause the rampant cases of early marriage in Indonesia and (4) government efforts in reducing the number of early marriages in Indonesia. This study concludes several things, including (1) early marriage is an engagement that occurs and is carried out by couples who are still classified as young or puberty, (2) according to the view of civil law, early marriage is at the age of the prospective husband or wife under nineteen years and is basically not allowed by law, but early marriage according to civil law can be done by obtaining permission from both parents and asking for marriage dispensation to the religious court with the right reasons, evidence and conditions. (3) the factors causing the prevalence of early marriage in Indonesia are social factors, health, family parenting, economy, easy access to information, customs and culture, education and religion, (4) efforts made by the government in reducing the number of early marriages are by conducting socialization, education, empowering women, conducting pre-marital guidance activities in schools and increasing knowledge to adolescents about the importance of reproductive health in an effort to prevent child marriage at an early age.